Association between expression of inflammatory markers in normal breast tissue and mammographic density among premenopausal and postmenopausal women. Issue 5 (May 2017) - Hanna, Mirette; Dumas, Isabelle; Orain, Michèle; Jacob, Simon; Têtu, Bernard; Sanschagrin, François; Bureau, Alexandre; Poirier, Brigitte; Diorio, Caroline
Abstract: Objective: Inflammatory markers may be associated with breast cancer risk. We assessed the association between expression levels of proinflammatory (interleukin 6, tumor necrosis factor-α, C-reactive protein, cyclooxygenase 2, leptin, serum amyloid A1, interleukin 8, and signal transducer and activator of transcription 3) and anti-inflammatory markers (transforming growth factor-β, interleukin 10, and lactoferrin) in normal breast tissue with mammographic density, a strong breast cancer risk indicator, among 163 breast cancer patients. Methods: The expression of inflammatory markers was visually evaluated on immunohistochemistry stained slides. The percent mammographic density (PMD) was estimated by a computer-assisted method in the contralateral cancer-free breast. We used generalized linear models to estimate means of PMD by median expression levels of the inflammatory markers while adjusting for age and waist circumference. Results: Higher expression levels (above median) of the proinflammatory marker interleukin 6 were associated with higher PMD among all women (24.1% vs 18.5%, P  = 0.007). Similarly, higher expression levels (above median) of the proinflammatory markers (interleukin 6, tumor necrosis factor-α, C-reactive protein, and interleukin 8) were associated with higher PMD among premenopausal women (absolute difference in the PMD of 8.8% [ P  = 0.006], 7.7% [ P  = 0.022], 6.7% [ P  = 0.037], and 16.5% [ P  = 0.032], respectively). Higher expression levels (above median) of the anti-inflammatory marker transforming growth factor-β were associated with lower PMD among all (18.8% vs 24.3%, P  = 0.005) and postmenopausal women (14.5% vs 20.7%, P  = 0.013). Conclusions: Our results provide support for the hypothesized role of inflammatory markers in breast carcinogenesis through their effects on mammographic density. Inflammatory markers could be targeted in future breast cancer prevention interventions. Abstract : Supplemental Digital Content is available in the text